The international style - Hitchcock, Henry-Russell, 1903-1987; Johnson, Philip, ....- (New York : W.W. Norton & Company, 1996)
Initially produced as the catalog to accompany a controversial and groundbreaking 1932 Museum of Modern Art show of the then new architecture emerging in Europe and America, The International Style quickly became the definitive statement of the principles underlying the work of such giants as Mies van der Rohe, Le Corbusier, Walter Gropius, and other pioneers. It might be said that Henry-Russell Hitchcock and Philip Johnson discovered as well as defined the International Style, and over the decades their book has served as both a flashpoint for criticism and a frame for growth in the architectural profession. It has never been out of print in over sixty years. This new edition has been completely redesigned and reset, and it features a new foreword by Philip Johnson, who reflects on the legacy of the International Style and examines the still-precarious power of architecture in our public life.